1998
DOI: 10.1109/20.703868
|View full text |Cite
|
Sign up to set email alerts
|

Eddy-current testing by flexible microloop magnetic sensor array

Abstract: A flexible microloop magnetic sensor array has been developed for nondestructive evaluation in nuclear power plants and its fundamental characteristics have been investigated. A flexible micro-eddy current testing (micro-ECT) probe consists of a pancake-type exciting coil of the diameter of 3.2 m and a flexible microloop magnetic sensor array with an area of 14 2 14 mm 2 and a thickness of 125 m. The array has 16 microloop sensors made of copper formed on a flexible polyimide film by sophisticated photolithogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 7 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…For testing the spatial distribution of the magnetic field by means of coil sensors the flexible microloop sensor array has been developed [26]. The array consists of 16 microloop sensors with an area of 14 × 14 mm 2 and a thickness of 125 µm.…”
Section: Design Of the Air-coil Sensormentioning
confidence: 99%
“…For testing the spatial distribution of the magnetic field by means of coil sensors the flexible microloop sensor array has been developed [26]. The array consists of 16 microloop sensors with an area of 14 × 14 mm 2 and a thickness of 125 µm.…”
Section: Design Of the Air-coil Sensormentioning
confidence: 99%
“…Its advantages include the flexibility ofattachment to a complex surface, high sensitivity and easy construction [74]. In recent years, the planar coil sensor has become an area ofinterest in many researches including analytical modeling of various sensor dimension designs [74][75][76] and magnetic field detection applications [77][78][79]. It has been reported that planar coil sensors have been successfully implemented in the ECT technique to inspect the PCBs [60,[80][81][82].…”
Section: Eddy Current Testing Techniquementioning
confidence: 99%
“…It has been proved as an effective tool for quantitative characterisation of hidden corrosion and cracks in multilayered aircraft structures [4,5], leading to the development of instruments for aircraft inspection [5][6][7][8][9]. For in-situ inspection for aerospace structures, various EC techniques are required, because each method has specific advantages, in multi-frequency excitation it is easy to classify defects at different depths [10], sensor arrays can inspect a large area [11] and alternating current field measurement (ACFM) can be used to evaluate defect depth [12]. Therefore, there is an increasing interest in developing an integrated portable EC instrument [13] with low cost and increased functionality.…”
Section: Introductionmentioning
confidence: 99%